Coherent control in hybrid metal-semiconductor nanostructures - Meier, Torsten; Reichelt, Matthias (DPG Spring meeting 2009)
Recently it has been shown experimentally that it is possible to coherently control nano-optical excitations by using sophisticated shaped laser pulses. In this work a similar technique is used to theoretically investigate a hybrid nanostructure which consists of a metal aperture and a quantum wire. It is shown that one can concentrate the optically excited electron density at an arbitrary position due to wave packet dynamics by chosing particular frequency components and phases of the chirped laser pulse. The optimization process is performed with a genetic algorithm which is linked to a 3D-FDTD solver.

Shaping the spatiotemporal dynamics of the electron density in a hybrid metal-semiconductor nanostructure - Reichelt, Matthias; Meier, Torsten (Optics Letters)
A one-dimensional semiconductor nanostructure is locally excited through a metal aperture. It is shown that the electron density can be coherently localized at desired spatial and temporal positions by using nontrivially shaped laser pulses. To obtain the optimized laser field, Bloch equations for a tight-binding model system are solved together with a genetic pulse-shaping algorithm. Full three-dimensional finite-difference time-domain (FDTD) simulations of the Maxwell–Bloch equations confirm the predicted coherent spatiotemporal control.

Generation of injection currents in (110)-oriented GaAs quantum wells: experimental observation and development of a microscopic theory - Bieler, M.; Pierz, K.; Siegner, U.; Dawson, P.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIII)
We have experimentally investigated injection currents generated by all-optical excitation of GaAs/AlGaAs quantum wells excited with 130 fs optical pulses. The currents have been detected via free-space THz experiments at room temperature. Our experiments prove that Coulomb effects strongly influence injection currents. This becomes most prominently visible when exciting light-hole exciton transitions. At this photon energy we observe a pronounced phase shift of the current transients which is due to oppositely oriented heavy-hole and light-hole type contributions. We are currently developing a microscopic theory based on a 14×14 k.p model in combination with the semiconductor Bloch equations to describe the observed features quantitatively. The combined theoretical and experimental approach will allow us to analyze the influence of the bandstructure and interaction effects on the injection current amplitude and current dynamics.
Keywords: tet_topic_qw

Microscopic theory of the linear and nonlinear Terahertz response of semiconductors - Meier, Torsten; Koch, S.W.; Kira, M.; Steiner, J.T.; Golde, D. (CLEO/Europe - EQEC 2009 - European Conference on Lasers and Electro-Optics and the European Quantum Electronics Conference)
The paper presents a theoretical analysis of the nonlinear THz response from the internal transitions of coherent and incoherent excitons based on the formulated microscopic THz theory. Moreover, the response of unexcited semiconductors to extremely intense THz fields is investigated .The intersubband transitions of optically excited quantum wells using linear THz spectroscopy is also studied. The computed differential transmission shows a characteristic Fano-like line shape of the intersubband resonance. The pure intersubband contribution is given by a simple Lorentzian. Applying the microscopic theory, the Fano features of the total response can be attributed to the phase-sensitive superposition of the intersubband transitions and the ponderomotive contribution. These results are in excellent agreement with recent experiments.

Ultrafast coherent photoelectron emission effects and their application for time-domain studies of current transport - Meier, Torsten; Koch, S.W.; Rohleder, M.; Gudde, J.; Hofer, U. (Conference on Lasers and Electro-Optics and 2009 Conference on Quantum electronics and Laser Science Conference)
By combining coherent control schemes and photoelectron spectroscopy it is possible to generate ultrafast current pulses at surfaces and in solids and to detect their decay directly in momentum space with femtosecond time resolution.

Determination of homogeneous and inhomogeneous broadenings of quantum-well excitons by 2DFTS: An experiment-theory comparison - Kuznetsova, Irina; Thomas, Peter; Meier, Torsten; Zhang, Tianhao; Cundiff, Steven T. (physica status solidi (c))
The recently developed two-dimensional Fourier-Transform-Spectroscopy (2DFTS) in the optical regime has been established as an elegant experiment, which has manifold of applications in the investigation of semiconductor nanostructures. Here we focus on the real and imaginary part 2DFT spectra. As predicted recently, using rephasing and non-rephasing modes, we are able to determine the homogeneous and inhomogeneous broadenings of coupled excitonic resonances even for weak disorder where photon-echo data are not useful. Computed real and imaginary parts of the 2DFTS for rephasing and non-rephasing modes are compared with experimental data of a GaAs quantum well. It is demonstrated, that phase sensitive data for the rephasing and non-rephasing modes are able to accurately provide the disorder induced broadening in a complex coupled system for each transition separately.

Microscopic analysis of high-harmonic generation in semiconductor nanostructures - Golde, Daniel; Meier, Torsten; Koch, Stephan W. (physica status solidi (c))
A microscopic analysis of the emitted radiation of a semiconductor nanostructure after excitation with an extremely intense ultrashort laser pulse is presented. It is shown that the extreme nonlinear optical response is not sufficiently described by pure interband transitions but one has to include intraband effects as well. Numerical solutions of extended Bloch equations that include the coupled inter- and intraband dynamics are presented. For large excitation intensities, the intraband effects strongly modify the polarization dynamics and lead to a strong enhancement of high-harmonic generation compared to pure interband dynamics.

Preface - Meier, Torsten; Michler, Peter (physica status solidi c)

Reiseprosa zwischen erlebter und erfundener Erfahrung von Wolfgang Büscher, Hape Kerkeling und Sigrid und Hamster Damm - Müller, Inez (Autobiographisches Schreiben in der deutschsprachigen Gegenwartsliteratur, Bd. 3: Entwicklungen, Kontexte, Grenzgänge.)

Photo-and spin current generation and dynamics in semiconductor nanostructures - Meier, Torsten; Duc, Huynh Thanh; Foerstner, Jens (DPG Spring meeting 2009)
The band structure and wave functions of GaAs quantum wells are computed via k.p band structure theory including anisotropy and spin splitting. Using these results, the process of generating photocurrents by optical excitation is analyzed. Depending on the symmetry of the material, the direction of the laser beam, and the polarization direction of the light field/s, one can coherently generate charge and/or spin photocurrents on ultrashort time scales. The direction, the strength, and the dynamics of these photocurrents are computed and discussed.

Datenbilder. Zur digitalen Bildpraxis in den Naturwissenschaften - Adelmann, Ralf; Frercks, Jan; Heßler, Martina; Hennig, Jochen

Rezension zu: Hüppauf, Bernd; Weingart, Peter (Hrsg.): Frosch und Frankenstein. Bilder als Medium der Popularisierung von Wissenschaften. Bielefeld 2009 - Adelmann, Ralf (H-Soz-u-Kult)

Selbst etwas tun. Handeln und Subjektkonstitution in Computerspielen (Vortrag an der HBK Braunschweig 9.2.2009) - Adelmann, Ralf; Winkler, Hartmut

Geschichten einfliegen? Dynamische Einstellungen in Film und Fernsehen - Adelmann, Ralf (Fasten Your Seatbelt! Bewegtbilder vom Fliegen)

Zurück zur Meisterlehre? Beurteilen lernen und beurteilt werden am Ausbildungsort Schule - Freitag, Christine (Seminar – Lehrerbildung und Schule 3/2009)

Wirkungen digitaler Medien - Herzig, Bardo; Grafe, S. (Schule in der digitalen Welt)

Selbstreguliertes Lernen fördern. - Herzig, Bardo; Aßmann, S.; Altmann, R. (mathematik lehren. Begriffe klären, Konzepte entwickeln, Schule verändern.152 (2009))

Gestaltung von Unterricht. Eine Einführung in die Didaktik - Tulodziecki, G.; Herzig, Bardo; Blömeke, S.

Unexpected Hydrogen Bond Dynamics in Imidazolium-Based Ionic Liquids - Thar, J.; Brehm, Martin; Seitsonen, A. P.; Kirchner, B. (J. Phys. Chem. B)

Digitale Medien in Schule und Alltagswelt. Zur Verbindung von formalen und informellen Lernprozessen - Herzig, Bardo; Grafe, S. (Medienbildung in neuen Kulturräumen: Aufgaben, Adressaten, Ansätze)

Mediendidaktik - Herzig, Bardo; Aßmann, S. (Handbuch der Erziehungswissenschaft. Band III: Familie, Kindheit, Jugend, Gender, Umwelten)

Verortungsprobleme von Schule in einer Netzwerkgesellschaft - Aßmann, S.; Herzig, Bardo (Schularchitektur im interdisziplinären Diskurs)

Kompetenzen in einer digital geprägten Kultur. Medienbildung für die Persönlichkeitsentwicklung, für die gesellschaftliche Teilhabe und für die Entwicklung von Ausbildungs- und Erwerbsfähigkeit. Bericht der Expertenkommission des BMBF zur Medienbildung - Schelhowe, H.; Grafe, S.; Herzig, Bardo

Schule als gestaltete und zu gestaltende Institution – ein systematischer Überblick über aktuelle und historische Schultheorien - Blömeke, S.; Herzig, Bardo (Handbuch Schule)

Bildungsstandards für die Medienbildung in internationaler Perspektive - Herzig, Bardo; Grafe, S. (medienimpulse Online 47(2009)1)

Professionelles Wissen und professionelle Handlungskompetenz von (angehenden) Physiklehrkräften - Riese, Josef

Fachbezogene Kompetenzmessung und Kompetenzentwicklung bei Lehramtsstudierenden der Physik im Vergleich verschiedener Studiengänge - Riese, Josef; Reinhold, Peter (Lehrerbildung auf dem Prüfstand)

Struktur und Entwicklung professionellen Wissens angehender Physiklehrer - Riese, Josef; Reinhold, Peter (Chemie- und Physikdidaktik für die Lehramtsausbildung. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Schwäbisch Gmünd 2008)

Structure and Development of Physics Student Teachers’ Professional Action Competence - Riese, Josef; Reinhold, Peter (NARST conference 2009, Conference Proceedings. Garden Grove)

Interkulturelle Kompetenz von Lehrkräften als Teilaspekt professionellen Handelns - Grimminger-Seidensticker, Elke (Evidenzbasierte Bildung. Wirkungsevaluation in Bildungspolitik und pädagogischer Praxis)

Schulinterne Sportlehrerfortbildungen als Schulentwicklungsinstrument - Die Förderung interkultureller Kompetenz von Sportlehrkräften - Grimminger-Seidensticker, Elke (Schulen in Bewegung - Schulsport in Bewegung)

Reflexive Interkulturalität als Schul(sport)entwicklungsperspektive - Die Laborschule in Bewegung - Grimminger-Seidensticker, Elke; Gieß-Stüber, P.; Schmerbitz, H.; Seidensticker, W. (Schulen in Bewegung - Schulsport in Bewegung)

Anerkennung und Zugehörigkeit im Schulsport - Überlegungen zu einer (Sport-)Pädagogik der Anerkennung - Grimminger-Seidensticker, Elke; Gieß-Stüber, P. (Anerkennung als sportpädagogischer Begriff)

Interkulturelle Kompetenz im Schulsport. Evaluation eines Fortbildungskonzepts - Grimminger-Seidensticker, Elke

Stand und Aufgaben der historischen Migrationsforschung in regionalgeschichtlicher Perspektive - Schubert, Michael (Migration und Gesellschaft seit dem 18. Jahrhundert am Beispiel Westfalens)

Kolonialpropaganda als Kolonialdiskurs. Die Disponibilität des ‚Negerbildes’ in der Deutschen Kolo-nialzeitung 1884–1914 - Schubert, Michael (Deutsche Sprache und Kolonialismus. Aspekte der nationalen Kommunikation 1884–1919)

Migration und Gesellschaft seit dem 18. Jahrhundert – am Beispiel Westfalens

Unintended effects of referral reward programs: Exploring the impact of rewards on opportunistic behavior - Garnefeld, I.; Münkhoff, Eva; Hogreve, J.; Eggert, A. (38th EMAC Annual Conference, Nantes)

Referral reward programs: New customer acquisition by opportunism? - Garnefeld, I.; Münkhoff, Eva; Hogreve, J.; Eggert, A. (15th AMS World Marketing Congress, Oslo)

Die Wahrnehmung handlungstriggernder Bedingungen im Sport - Güldenpenning, Iris; Schack, Thomas (Informations- und Kommunikationstechnologien in der Sportmotorik. Abstractband zur 11. Tagung der dvs-Sektion Sportmotorik)

Temporale Relationen interner Bewegungsrepräsentationen - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias; Schack, Thomas (Menschen in Bewegung - Sportpsychologie zwischen Tradition und Zukunft. 41. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

IMORC: Application Mapping, Monitoring and Optimization for High-Performance Reconfigurable Computing - Schumacher, Tobias; Plessl, Christian; Platzner, Marco (Proc. Int. Symp. on Field-Programmable Custom Computing Machines (FCCM))
Mapping applications that consist of a collection of cores to FPGA accelerators and optimizing their performance is a challenging task in high performance reconfigurable computing. We present IMORC, an architectural template and highly versatile on-chip interconnect. IMORC links provide asynchronous FIFOs and bitwidth conversion which allows for flexibly composing accelerators from cores running at full speed within their own clock domains, thus facilitating the re-use of cores and portability. Further, IMORC inserts performance counters for monitoring runtime data. In this paper, we first introduce the IMORC architectural template and the on-chip interconnect, and then demonstrate IMORC on the example of accelerating the k-th nearest neighbor thinning problem on an XD1000 reconfigurable computing system. Using IMORC's monitoring infrastructure, we gain insights into the data-dependent behavior of the application which, in turn, allow for optimizing the accelerator.
Keywords: IMORC; interconnect; performance

EvoCaches: Application-specific Adaptation of Cache Mapping - Kaufmann, Paul; Plessl, Christian; Platzner, Marco (Proc. NASA/ESA Conference on Adaptive Hardware and Systems (AHS))
In this work we present EvoCache, a novel approach for implementing application-specific caches. The key innovation of EvoCache is to make the function that maps memory addresses from the CPU address space to cache indices programmable. We support arbitrary Boolean mapping functions that are implemented within a small reconfigurable logic fabric. For finding suitable cache mapping functions we rely on techniques from the evolvable hardware domain and utilize an evolutionary optimization procedure. We evaluate the use of EvoCache in an embedded processor for two specific applications (JPEG and BZIP2 compression) with respect to execution time, cache miss rate and energy consumption. We show that the evolvable hardware approach for optimizing the cache functions not only significantly improves the cache performance for the training data used during optimization, but that the evolved mapping functions generalize very well. Compared to a conventional cache architecture, EvoCache applied to test data achieves a reduction in execution time of up to 14.31% for JPEG (10.98% for BZIP2), and in energy consumption by 16.43% for JPEG (10.70% for BZIP2). We also discuss the integration of EvoCache into the operating system and show that the area and delay overheads introduced by EvoCache are acceptable.
Keywords: EvoCache; evolvable hardware; computer architecture

PermaDAQ: A Scientific Instrument for Precision Sensing and Data Recovery in Environmental Extremes - Beutel, Jan; Gruber, Stephan; Hasler, Andi; Lim, Roman; Meier, Andreas; Plessl, Christian; Talzi, Igor; Thiele, Lothar; Tschudin, Christian; Woehrle, Matthias; Yuecel, Mustafa (Proc. Int. Conf. on Information Processing in Sensor Networks (IPSN))
Keywords: WSN; PermaSense

Communication Performance Characterization for Reconfigurable Accelerator Design on the XD1000 - Schumacher, Tobias; Süß, Tim; Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on ReConFigurable Computing and FPGAs (ReConFig))
Keywords: IMORC; graphics

An Accelerator for k-th Nearest Neighbor Thinning Based on the IMORC Infrastructure - Schumacher, Tobias; Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on Field Programmable Logic and Applications (FPL))
Keywords: IMORC; NOC; KNN; accelerator

Woolcano: An Architecture and Tool Flow for Dynamic Instruction Set Extension on Xilinx Virtex-4 FX - Grad, Mariusz; Plessl, Christian (Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA))
In this paper, we introduce the Woolcano reconfigurable processor architecture. The architecture is based on the Xilinx Virtex-4 FX FPGA and leverages the Auxiliary Processing Unit (APU) as well as the partial reconfiguration capabilities to provide dynamically reconfigurable custom instructions. We also present a hardware tool flow that automatically translates software functions into custom instructions and a software tool flow that creates binaries using these instructions. While previous research on processors with reconfigurable functional units has been performed predominantly with simulation, the Woolcano architecture allows for exploring dynamic instruction set extension with commercially available hardware. Finally, we present a case study demonstrating a custom floating-point instruction generated with our approach, which achieves a 40x speedup over software-emulated floating-point operations and a 21% speedup over the Xilinx hardware floating-point unit.

Walking Bus - der aktive Schulweg. Intervention und Evaluation. Endbericht - Brettschneider, Wolf-Dietrich; Kehne, Miriam

"Walking Bus" - Der aktive Schulweg - Kehne, Miriam; Brandl-Bredenbeck, Hans-Peter (Praxis der Psychomotorik)

Alltägliche Lehrerreflexion - Intuition oder Information? - Jonas-Ahrend, Gabriela; Wilbers, Jens
Im Projekt DOPPLER (Dortmunder Projekt Physik Lehren und Lernen) arbeiten Teams von Lehrkräften und Fachdidaktikern gemeinsam an der Erstellung neuer Unterrichtsmaterialien, die teilweise auch in der Praxis eingesetzt werden. Der Unterricht und auch die Teamsitzungen wurden aufgezeichnet. Im Verlauf der mehrjährigen Zusammenarbeit konnten vielfältige Informationen zu Lehrerkognitionen gewonnen werden. Die Auswertung der Teamsitzungen führte u.a. auch zu der Frage, inwiefern Lehrkräfte über ihren eigenen Unterricht alltäglich reflektieren. Es wurden strukturierte Interviews zum individuellen Planungs- und Reflexionsverhalten durchgeführt. Im Vortrag wird auf das alltägliche (also nicht videobasierte) Reflexionsverhalten von Physiklehrkräften eingegangen. Insbesondere wird der Frage nachgegangen, inwiefern Planungsprozesse durch individuelle Reflexionsprozesse beeinflusst werden.